2010
DOI: 10.1007/s00421-009-1344-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intra-abdominal pressure and spontaneous breath volume by magnitude of lifting effort: highly trained athletes versus healthy men

Abstract: Intra-abdominal pressure (IAP) is closely related to breathing behavior during lifting. Abdominal muscles contribute to both IAP development and respiratory function. The purpose of this study was to examine whether spontaneous breath volume and IAP altered with increased isometric lifting effort, and to compare the effect of different abdominal muscle strengths on these parameters. Maximal IAP during the Valsalva maneuver (maxIAP) and maximal isometric trunk flexor strength were measured in 10 highly trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…Furthermore, the quantity of inspired volume has been shown to be significantly related to the magnitude of mechanical challenge to the lumbar spine during a lifting task. 15,28,29 The sum of this evidence, therefore, suggests that dysfunction of the respiratory system or a dysfunction of coordination between the respiratory and postural muscular systems may impact segmental control of the lumbar spine.…”
Section: T T Conclusionmentioning
confidence: 99%
“…Furthermore, the quantity of inspired volume has been shown to be significantly related to the magnitude of mechanical challenge to the lumbar spine during a lifting task. 15,28,29 The sum of this evidence, therefore, suggests that dysfunction of the respiratory system or a dysfunction of coordination between the respiratory and postural muscular systems may impact segmental control of the lumbar spine.…”
Section: T T Conclusionmentioning
confidence: 99%
“…Our recent study showed that the maximal intra-abdominal pressure (IAP) during abdominal bracing was greater than during trunk flexion, trunk extension, and abdominal hollowing exercises . IAP is considered to be an important factor not only for enhancing the stability and stiffness of the spine (Essendrop et al 2002;Essendrop and Schibye 2004), but also for generating muscle force during kinetic chain activities such as lifting (Kawabata et al 2010). Taking these findings into account together with the aforementioned concept of core stabilization training, it is likely that a training program that includes abdominal bracing can be an efficacious modality for improving the strength and power of the trunk and lower limb muscles by increasing IAP.…”
Section: Introductionmentioning
confidence: 98%
“…It is known that intra-abdominal pressure is maintained to normal or even slightly increased, even there are abdominal or parietal factors witch act positively. This is due to the degree of elasticity of the abdominal muscle wall which are able to take on some of the positive charges until reaching a critical point (usually IAP >15 mmHg) after, the intra-abdominal pressure increases suddenly [1]. Thus the degree of myorelaxation corresponding TOF ratio<2 was not enough to significantly alter the intra-abdominal pressure, exceeding this threshold instead led to sudden increases in intra-abdominal pressure in all analyzed.…”
Section: Discussionmentioning
confidence: 90%
“…It is well known that the intraabdominal pressure (IAP) shows very wide variations in certain physiological or pathological condition such as changing the position of standing in supine exercise, coughing, sneezing, Valsalva maneuver [1]. Thus, different studies in the literature, report abdominal pressure values between 16 mmHg, 20 mmHg in standing 25-30 mmHg during exercise to lift a weight of 5 kg and the highest values of 06 mmHg -171 mmHg was recorded during coughing, sneezing or jumping.…”
Section: Introductionmentioning
confidence: 99%